A BRIEF HISTORY OF THE WOMEN'S BASKETBALL SECTION FROM UNIVERSITATEA CLUJ SPORTS CLUB 1955 - 1972 - Ildiko MANASSES; Ştefan MAROTI (Cluj University Press, 2016)
The present paper is part of a larger endeavour by means of which the authors, based on a varied research, are trying to present seventeen years of the women's basketball team's history, given the approaching 100th anniversary of Universitatea Cluj Sports Club. The first part focuses on the accomplishments, as well as on the weak results that followed after the team won the national championships in 1953 and 1954. The body of the paper is dedicated to the period 1960 - 1972, strongly marked by Vasile Geleriu, one of the iconic specialists of the team, who decisively influenced the fate of Cluj-Napoca university basketball. File din istoria secției de baschet feminin din cadrul Clubului Sportiv Universitatea Cluj-Napoca 1955-1972. Lucrarea este parte a unor eforturi prin care autorii, în preajma a o sută de ani de la constituirea Societății Sportive a Studenților Universității din Cluj, pe baza unei vaste documentări, prezintă trecutul echipei de baschet feminin. În prima parte, lucrarea se referă la împlinirile și contraperformanțele din anii care au urmat cuceririi titlurilor de campioane din anii 1953 și 1954. Partea cea mai consistentă prezintă perioada 1960 - 1972, care a fost marcată de activitatea unuia dintre specialiștii emblematici, Vasile Geleriu, care a influențat hotărâtor destinele baschetului feminin universitar din Cluj-Napoca.  Cuvinte cheie: baschet feminin, Universitatea, Cluj-Napoca, 1955 - 1972